Côte d'Ivoire bid to save forests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In a bid to save its forests from extinction, the Government of e d'lvoire has announced that it will ban all timber exports as soon as the country's budget can bear the loss. The forests of Cote d'lvoire are one of the world's principal sources of...